2012
DOI: 10.1038/nchembio.941
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive regulation of anapleurosis via allosteric activation of PEP carboxylase

Abstract: Anapleurosis is the filling of the TCA cycle with four-carbon units. The common substrate for both anapleurosis and glucose phosphorylation in bacteria is the terminal glycolytic metabolite, phosphoenolpyruvate (PEP). Here we show that E. coli quickly and almost completely turns off PEP consumption upon glucose removal. The resulting build-up of PEP is used to quickly import glucose if it becomes re-available. The switch-like termination of anapleurosis results from depletion of fructose-1,6-bisphosphate (FBP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 52 publications
(52 reference statements)
7
68
0
Order By: Relevance
“…3C). This finding is consistent with the magnified effects of allosteric activators on anaplerotic PEPC from Escherichia coli in the presence of inhibitors (Xu et al, 2012) and may further contribute to PEPC's in vivo activation during proteoid root maturation.…”
Section: Kinetic Properties Of Proteoid Root Pepcsupporting
confidence: 77%
“…3C). This finding is consistent with the magnified effects of allosteric activators on anaplerotic PEPC from Escherichia coli in the presence of inhibitors (Xu et al, 2012) and may further contribute to PEPC's in vivo activation during proteoid root maturation.…”
Section: Kinetic Properties Of Proteoid Root Pepcsupporting
confidence: 77%
“…We initially found that feedback inhibition alone is sufficient to enable both intracellular metabolite concentration homeostasis and optimal steady-state fluxes (Goyal et al, 2010). More recently, we demonstrated that feed forward regulation is important in oscillating conditions (Xu et al, 2012a;Xu et al, 2012b). In general, our experimental and computational results support a primary paradigm for nutrient integration: Limitation for a nutrient other than carbon leads to build-up of the most closely related product of carbon metabolism, which in turn feedback inhibits further carbon utilization.…”
Section: Aim 3: Gain Insight Into the Key Principles Underlying The Csupporting
confidence: 50%
“…These point mutants which lack positive regulation of anaplerosis by fructose-1,6-bisphosphate, a key metabolite indicating high sugar availability. Such mutants grow normally in steady glucose but are strikingly deficient in an oscillating glucose environment (Xu et al, 2012a;Xu et al, 2012b). Related work investigates additional nutrients and stresses, and the robustness of biological responses to them (Goodarzi et al, 2010;Hart et al, 2011;Peterson et al, 2012;Reaves and Rabinowitz, 2011a, b).…”
Section: Aims Summary Aim 1: Reveal the Interplay Between Different Nmentioning
confidence: 99%
“…As a result, PKI activity remains fairly low consistent with the physiological needs of the cell. However, when glucose becomes available again, it is rapidly imported by consuming the accumulated PEP triggering rapid accumulation of FBP and an increase in the ATP/ADP ratio, which activates key glycolytic enzymes [68]. This response is responsible for the rapid adaptation of E. coli to …”
Section: Accepted M Manuscriptmentioning
confidence: 99%